Single-molecule fluorescence imaging techniques reveal molecular mechanisms underlying deoxyribonucleic acid damage repair - Kang, Yujin; An, Soyeong; Min, Duyoung; Lee, Ja Yil (Frontiers in Bioengineering and Biotechnology, 2022)
Advance of single-molecule techniques has uncovered numerous biological secrets that could not be disclosed by traditional methods. Among a variety of single-molecule techniques, single-molecule fluorescence imaging techniques enable real-time visualization of biomolecular interactions and adduce convincing evidence. They have been broadly applied for studying DNA metabolic events such as replication, transcription, and DNA repair, which are all the most fundamental biological reactions. In particular, DNA repair is intensively paid attention to because it maintains genomic integrity and is associated with diverse human diseases. In this review, we introduce representative single-molecule fluorescence imaging techniques and survey how each technique has been employed for investigating detailed mechanisms underlying DNA repair pathways. In addition, we briefly show how live cell imaging at the single-molecule level contributes to understanding DNA repair processes inside a cell.